First report of complete chloroplast genome sequence of monotypic genus Astilboides (Saxifragaceae) in North East Asia. Issue 3 (2nd July 2020) - Ha, Young-Ho; Gil, Hee-Young; Kim, Dong-Kap
Abstract: The complete chloroplast genome sequence of Astilboides tabularis, one of endemic species of Eastern Asia, was determined. The chloroplast genome was 157, 147 bp in length with large single-copy (87, 703 bp), small single-copy (18, 268 bp) and a pair of inverted repeats (25, 588 bp). In total, 131 genes were encoded, including 86 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The phylogenetic analysis using concatenated 77 protein-coding genes of 15 species chloroplast genome revealed that A. tabularis was sister to the clade containing Bergenia, Oresitrophe, and Mukdenia .